CALCULATIONS ON RENUMERATION OF LABOR WITH THE SOCIAL INSURANCE BODIES IN THE COMPANY’S REPORTING - Galushchak, I.Ye. (The actual problems of regional economy development, 2019)
The purpose of this article is to review the general rules and trends in the legal regulation of renumeration of labor with social security bodies in the company’s reporting; peculiarities of displaying of renumeration of labor in the company's reporting, outline the main areas of improvement of renumeration of labor with social security agencies. The article deals with the peculiarities of calculations on renumeration of labor with the social insurance bodies in the company’s reporting. The problems in keeping records of work, accrual and payment of wages are encountered. The basic directions of improvement at realization of calculations on renumeration of labor with social insurance bodies are outlined. The calculation on renumeration of labor in the company’s reporting is shown. The data of the status of renumeration of labor in the financial reporting are reflected. Data on renumeration of labor are reflected in the financial, statistical, tax, and specialty statements. The legislative and regulatory regulation of accounting and analysis of remuneration and payments of labor with social insurance bodies is investigated. The main document that defines the economic and organizational principles of remuneration of employees who are in employment relations, on the basis of an employment contract with enterprises, institutions, organizations of all forms of ownership and management, as well as with individual citizens and areas of state and contractual regulation of renumeration of labor of Ukraine “On renumeration of labor”. It aims to provide the reproductive and stimulating functions of wages. It is determined that the main forms of renumeration of labor are part-time and hourly, and social insurance systems are divided into voluntary and compulsory social insurance.